Using College Students as Peer Leaders in a Tobacco Prevention Program and the Effect on Student Participant Smoking Beliefs and Social Influence Leadership - Elizabeth A Kleitz; Namuna Sunar; Greenlee Rigby (Undergraduate Research Journal for the Human Sciences, 2024)
This study evaluates the effectiveness of using college students as peer leaders in an after-school tobacco prevention program for upper elementary students. Thirty-three students and three counselors participated in a six-week intervention, focusing on social influence and active-learning strategies. The program aimed to improve students' smoking outcome expectancies and their ability to influence peers against tobacco use. Despite following best practices, the study found no significant changes in students' smoking beliefs or observed leadership abilities. These results suggest that while initial anti-tobacco beliefs remained strong, the short duration and structured setting may have limited opportunities for significant behavioral changes. This study highlights the importance of exploring diverse and non-traditional settings for tobacco prevention education and suggests further research with larger samples and varied contexts to better understand the potential impact of peer-led interventions.
Keywords: elementary; tobacco prevention; beliefs; social influence; peer leaders